International Musicals Opera Theatre Of Solo - Warastri, Ristiana; , Dr. Ir. Dhani Mutiari, MT (2016)
The development of performing arts in the world runs so fast. Performing arts theater to have some kind of different in each country which are in Europe. Opera is an art that combines music, vocal, dance, and dialogue. Containers of art works to accommodate the activities of the artist that is the result of good work of art and then presented to the public. The theater is one place to facilitate the activities of art that is both visual and audio enjoyment as group singing, dance, and drama. The lack of adequate facilities to accommodate the performing arts in Surakarta is one of the background for the planning and design of the International Musicals Opera Theatre of Solo. Solo city chosen for the city of Solo is a city of culture. The problem faced is how to create the theater arts (theater) based on standard theater arts which includes aspects of lighting, visual, and acoustic. Flexibility in the stage in a performance art as a means of supporting a staging. Showing buildings (exterior and interior) with the concept of metaphor as aesthetics and identity building, and determine the location of the site is strategically support for the International Musicals Opera Theatre of Solo. By identifying the existing problems with its components in stages, then analyze the problem based on the requirements and standards applicable to later summed up as a benchmark in the manufacture concept planning and design in the form of a framework of targeted and integrated form of description of the concept of planning and design.